Cavernous Transformation of the Portal Vein in a 26-Month Old Boy Treated by Transjugular Intrahepatic Portosystemic Shunt: A Case Report - Wei, Bo; Zhang, Linhao; Tong, Huan; Wang, Zhidong; Wu, Hao (Frontiers in Pediatrics, 2019)
Cavernous transformation of portal vein (CTPV) is the main cause of portal hypertension and its related variceal bleeding in children. Transjugular intrahepatic portosystemic shunt (TIPS) was not reported to treat CTPV for children younger than 5-year old. In this case report, the patient was a 26-month boy who presented with haematemesis and melena due to CTPV. Even after azygoportal disconnection, repeated haematemesis as well melena still happened. After careful evaluation, we performed TIPS under general anesthesia for him. The procedure was uneventful and 6 mm stents were placed. Six-month after TIPS, bleeding did not recur and no procedure-related event happened. The follow-up esophagogastroduodenoscopy proved dramatic remission of varices, indicating a successful outcome. We believe TIPS could be safely placed for young children to manage variceal bleeding due to CTPV.